THE IMPACT OF GLOBALIZATION AND THE INDIAN DIASPORA ON THE ECONOMIC DEVELOPMENT OF SEYCHELLES - Neha Nikita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Globalization has had a profound impact on economies worldwide through its effects on investment, commerce, labor mobility and intercultural interactions. Globalization has enabled small island economies, such as the Seychelles, to diversify their economy, strengthen their trading networks and attract more foreign direct investment. With an emphasis on the impact of the Indian diaspora, this study investigates the relationship between globalization and economic growth in the Seychelles. It focuses on how commerce, investment and job prospects have been made easier by globalization, as well as how the Indian population has impacted a variety of economic sectors, including as manufacturing, banking, tourism, healthcare and education. The research also looks at the challenges faced by the Indian diaspora in Seychelles and the broader impacts of globalization on the bilateral economic relations, labor markets and entrepreneurship between India and Seychelles. The study concludes that strengthening commercial relationships and diaspora engagement is important for sustaining Seychelles’ economic success.